Давньоруські старожитності Східної Волині у матеріалах досліджень та в експозиції археологічного відділу Волинського Центрального Науково-Дослідного музею (1919—1931 рр.) - Тарабукін, О.О. (Археологія і давня історія України, 2016)
У статті висвітлюється діяльність археологічного відділу Волинського центрального науково-дослідного музею у вивчені давньоруських старожитностей на теренах Східної Волині, а також побудови на основі зібраних матеріалів експозиції музейної секції
відділу, присвяченій історії краю за доби Київської
Русі. Наводяться результати польових досліджень, відомості про виявленні об'єкти і окремі знахідки. В первой трети ХХ ст. важное место в изучении
древностей Восточной Волыни занимал археологический отдел Волынского центрального научно-исследовательского музея. Во время проведения
полевых исследований в разных уголках края сотрудниками отдела выявлено значительное количество разнообразных объектов и отдельных находок широкого хронологического диапазона, охватывая период от каменного века до позднего средневековья
включительно. Определенный интерес представляет деятельность отдела по регистрации и изучению
древностей древнерусского периода, сбору материалов и созданию на их основе раздела экспозиционной части музейной секции, посвященной истории края в эпоху раннего и развитого средневековья. In 1st third of 20th century of item an important place
in the study of antiquities of East Volyn’ was occupied
by the archaeological department of the Volyn’ central
research museum. Certain interest presents activity of
department on the study of antiquities of the Ancient
Rus’ period. During the field researches on territories
Zhytomyr and Korosten’ of neighborhoods was educed
more than 60 objects of period of Kyiv Rus’. Medieval
antiquities of cities of Zhytomyr, annalistic Ovruch and
Korosten’ were studied. Tasks were put the connections
of sites of ancient settlement sent to finding out with
burial mound burial grounds and their maintenance. An inspection and collection of lifting material came true
from monuments related to the booty and treatment of pirofilit slate. Burial mounds were mainly dug out. Beginning
of stationary research of one of sites of ancient settlement of annalistic Iskorosten’ is fixed in 1925. On
the basis of the collected materials the division of display of museum section of department that was summarize
the results of long-term study of monuments of the Ancient Rus’ period of East Volyn’ is created.